2017
DOI: 10.1007/5584_2017_40
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Against Salmonella Enteritidis Is Unsettled by HIV Infection

Abstract: The human immunodeficiency virus (HIV) is responsible for more than 2 million new infections per year and opportunistic infections such as Salmonella spp. Gastroenteritis is an important cause of mortality and morbidity in developing countries. Monocytes and macrophages play a critical role in the innate immune response against bacterial infections. However during HIV infection the virus can infect these cells and although they are more resistant to the cytopathic effects, they represent an important viral res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The severity of iNTS in PLWH may be due to an impaired immune response to the infection, as suggested in a study by MacLennan et al [ 84 ]; specifically, it was reported that an excess of antibodies against Salmonella lipopolysaccharide (LPS) is associated with a reduction in Salmonella killing. Other reasons behind the severity of iNTS in PLWH may be found in the dysregulation of proinflammatory cytokine release, such as TNF alpha, IL-10 and IL-12 [ 85 ], the attenuation of transcription factor nuclear κB (NFκB)-mediated inflammation [ 86 ], the defective activity of monocytes phagocytosis [ 87 ] and the apparent enhanced capacity of a specific sequence type 313 (ST313) of S. typhimurium of surviving in HIV-infected macrophages and their defective phagocytic ability [ 88 , 89 ].…”
Section: Salmonellosismentioning
confidence: 99%
“…The severity of iNTS in PLWH may be due to an impaired immune response to the infection, as suggested in a study by MacLennan et al [ 84 ]; specifically, it was reported that an excess of antibodies against Salmonella lipopolysaccharide (LPS) is associated with a reduction in Salmonella killing. Other reasons behind the severity of iNTS in PLWH may be found in the dysregulation of proinflammatory cytokine release, such as TNF alpha, IL-10 and IL-12 [ 85 ], the attenuation of transcription factor nuclear κB (NFκB)-mediated inflammation [ 86 ], the defective activity of monocytes phagocytosis [ 87 ] and the apparent enhanced capacity of a specific sequence type 313 (ST313) of S. typhimurium of surviving in HIV-infected macrophages and their defective phagocytic ability [ 88 , 89 ].…”
Section: Salmonellosismentioning
confidence: 99%